Plan evaluation in radiotherapy: on the way to automated treatment planning - Ventura, Tiago Emanuel Pereira (2022)
Radiation therapy makes use of ionization radiation to eliminate in a controlled way tumours cells sparing as much as possible the normal tissues. The treatment is delivered to the patient during several sessions according to a personalized plan optimized a priori by a planner in a treatment plan system. The most advanced planning techniques, such as inverse planning optimization of static beams or volumetric arcs, require the use of dose optimization algorithms, that allow the planner to find one or more solutions that satisfies as much as possible the prescription dose for the target and the tolerance dose criteria for the normal tissues. Treatment plan automation based on multicriteria optimization algorithms generates treatment planning solutions with equivalent dose distribution quality and reduced the interaction from the planner. The quality of the dose distribution can even be substantially enhanced when beam angle optimization and arc trajectory optimization algorithms are incorporated in plan optimization. The main purpose of this work is to contribute to the treatment planning automation process by developing new plan assessment tools and use them for testing new directions/trajectory optimization algorithms. To support clinical decision-making, a graphical method incorporating the clinical aims of the radiation oncologist was developed to evaluate and compare treatment plans independently from the algorithm, the treatment technique or the treatment planning system used. This plan quality assessment tool, named SPIDERplan, was clinically validated for the nasopharynx pathology by three radiation oncologists from the three Portuguese Oncology Institutes in Lisbon, Porto and Coimbra. The performance of SPIDERplan proved to be comparable with the radiation oncologists’ evaluations. Its configuration and resulting scoring were discussed enabling its generalized application. SPIDERplan was then extensively used. Firstly, for nasopharynx tumour cases, in the comparison of two-fluence based beam angle optimization algorithms for coplanar and non-coplanar geometries in a multicriterial optimization framework. The direction optimization topic was afterwards extended to intracranial tumours, namely to meningioma cases. SPIDERplan was used, this time, not just to assess plans quality but also to guide the non-coplanar beam angle optimization algorithm. Furthermore, a new arc trajectory optimization algorithm based in the anchor point concept was proposed, driven again by SPIDERplan. In both nasopharynx and meningioma pathologies, SPIDERplan was used to assess the plans quality, averaged over the used patient samples. In addition, its application to specific-patient situations enabled to evidence the advantages of the optimization of direction/trajectory in a very impressive way.